Performance of HPV16/18 in Triage of Cytological Atypical Squamous Cells of Undetermined Significance - Xiaoqin Cao; Shuzheng Liu; Manman Jia; Hongmin Chen; Dongmei Zhao; Bing Dong; Zhen Guo; Lingyan Ren; Shaokai Zhang; Xibin Sun (Analytical Cellular Pathology)
Context. Human papillomavirus (HPV) testing is widely used in cervical cancer screening in women; however, its efficiency in triaging women with atypical squamous cells of undetermined significance (ASC-US) needs to be validated. Objective. To evaluate the performance of HPV16/18 in the triage of women with ASC-US. Methods. Women presenting for routine cervical cancer screening had cervical specimens collected, with which both liquid-based cytology (LBC) and hrHPVs were examined; those with ASC-US cytology underwent colposcopy. HPV16/18 and 12 other types were tested with domestic hybridization capture and chemiluminescence signal amplification (DH3). Performance characteristics of HPV test (sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) for identification of cervical intraepithelium neoplasma (CIN) grade 2 or worse (CIN2+), and CIN grade 3 or worse (CIN3+)) were determined using standard statistical tests. Results. 317 women with ASC-US were eligible for the study. HrHPV prevalence was 15.77% (50/317); HPV16/18 prevalence was 3.61% (20/317). Sensitivity and specificity of HPV16/18 for detection of CIN 2+ were 64.71% and 97% and 64.29% and 96.37% for detection of CIN 3+, respectively. The positive predictive values (PPVs) and negative predictive values (NPVs) of HPV16/18 were 55.00% and 97.98% for CIN2+ and 45.00% and 98.32% for CIN3+, respectively. Conclusion. HPV16/18 can be considered as an effective method to triage women with ASC-US as its good clinical performance. Trial Registration. This trial is registered with Henan Cancer Hospital Medical Ethics Committee on July 5, 2016 (http://www.anti-cancer.com.cn), with registry no.: 2016037.